Seasonal variation in the soil fungal community structure of Larix gmelinii forests in Northeast China - Zhao, Wen; Wang, Dan-Dan; Huang, Kai-Chuan; Liu, Shun; Reyila, Mumin; Sun, Yi-Fei; Li, Jun-Ning; Cui, Bao-Kai (Frontiers in Microbiology, 2023)
Soil fungi play an indispensable role in forest ecosystems by participating in energy flow, material circulation, and assisting plant growth and development. Larix gmelinii is the dominant tree species in the greater Khingan Mountains, which is the only cold temperate coniferous forest in China. Understanding the variations in underground fungi will help us master the situation of L. gmelinii above ground. We collected soil samples from three seasons and analyzed the differences in soil fungal community structure using high-throughput sequencing technology to study the seasonal changes in soil fungal community structure in L. gmelinii forests. We found that the Shannon and Chao1 diversity in autumn was significantly lower than in spring and summer. The community composition and functional guild varied significantly between seasons. Furthermore, we showed that ectomycorrhizal fungi dominated the functional guilds. The relative abundance of ectomycorrhizal fungi increased dramatically from summer to autumn and was significantly negatively correlated with temperature and precipitation. Temperature and precipitation positively affect the alpha diversity of fungi significantly. In addition, pH was negatively correlated with the Chao1 diversity. Temperature and precipitation significantly affected several dominant genera and functional guilds. Among the soil physicochemical properties, several dominant genera were affected by pH, and the remaining individual genera and functional guilds were significantly correlated with total nitrogen, available phosphorus, soil organic carbon, or cation exchange capacity. For the composition of total fungal community, temperature and precipitation, as well as soil physicochemical properties except AP, significantly drove the variation in community composition.